ANALISIS HISTOLOGIS GINJAL, HATI DAN JANTUNG IKAN LELE AFRIKA Clarias gariepinus YANG MENGALAMI ANOMALI PADA SIRIP PEKTORAL - Hidayatul Laily; Farikhah Farikhah; Ummul Firmani (Jurnal Perikanan Pantura (JPP), 2018)
The purpose of this study was to describe the histology of kidney, liver and heart organs in African catfish Clarias gariepinus not pectoral fin which originated from maintenance in aquaculture ponds. The study was conducted in June 2018 at the Reproductive Laboratory of Fisheries Cultivation Study Program, Department of Water Resources Management, Faculty of Fisheries and Marine Sciences, Brawijaya University, Malang. This research method is descriptive of the object under study that is abnormal fish and the sample specified is 3 individuals. There are 3 target organs, namely kidney, liver and heart. As a comparison, a normal fish sample is used, which is a complete pectoral fin fish. Each organ is examined by the parts that most play a role in the function of the organ. The results of the study showed that abnormal African catfish glomelurus underwent changes that merged with the bowman capsule, whereas in the liver it was found that the hepatocyte nucleus was shrinking and fading. In the heart organ the pericardium layer appears thinner